KONTRIBUSI PENGUASAAN KOSAKATA TERHADAP KETERAMPILAN MENULIS TEKS BERITA SISWA KELAS VIII SMP NEGERI 1 SINTUK TOBOH GADANG - Ihsan M. Zikra; Yulianti Rasyid (Universitas Negeri Padang, 2020)
ABSTRACTThe purpose of this study is (1) describes the vocabulary mastery of VIII grade students of SMP Negeri 1 Sintuk Toboh Gadang, (2) describe the news text writing skills of eighth grade students of SMP Negeri 1 Sintuk Toboh Gadang, and (3) analyze the contribution of vocabulary mastery to news writing skills of eighth grade students of SMP Negeri 1 Sintuk Toboh Gadang. This type of research is quantitative research with descriptive methods. Contributions are calculated using the determinant coefficient formula with correlational research design. The population of this research is the eighth grade students of SMP Negeri 1 Sintuk Toboh Gadang in the 2018/2019 school year with a total of 219 people spread over eight classes. The sample of this study was 136 people, taken using propotional random sampling. Based on the results of the study, it is known that (1) the vocabulary mastery of Grade VIII students of SMP Negeri 1 Sintuk Toboh Gadang is more than adequate with a value of 67.34, (2) news writing skills of VIII grade students of SMP Negeri 1 Sintuk Toboh Gadang are in good qualifications with a value of 81.43, (3) there is a significant relationship between vocabulary mastery and news text writing skills of Grade VIII students of SMP Negeri 1 Sintuk Toboh Gadang with a count of 0.222 greater than rtable 0.168 at dk = 135 alpha 0.05 with a contribution of X to Y of 4.06%.Kata Kunci: kontribusi, kosakata, teks berita